2014
DOI: 10.1111/ecog.00670
|View full text |Cite
|
Sign up to set email alerts
|

Are different facets of plant diversity well protected against climate and land cover changes? A test study in the French Alps

Abstract: Climate and land cover changes are important drivers of the plant species distributions and diversity patterns in mountainous regions. Although the need for a multifaceted view of diversity based on taxonomic, functional and phylogenetic dimensions is now commonly recognized, there are no complete risk assessments concerning their expected changes. In this paper, we used a range of species distribution models in an ensemble-forecasting framework together with regional climate and land cover projections by 2080… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
78
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 83 publications
2
78
0
Order By: Relevance
“…This trend is comparable with the distribution of endemic species described for the Iberian Peninsula, where mountain ranges exhibit a great diversity of species, at least of the widespread type (Buira et al, 2017). In addition to land-use changes, changes in climate, notably a warming climate, are expected to strongly impact biodiversity in mountain environments Pauli et al, 2012;Stöcklin et al, 2009;Thuiller et al, 2014). Species are expected to migrate upward to keep pace with suitable climates, which should lead to an increase of diversity in higher altitudes in the near term (Walther et al, 2005).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This trend is comparable with the distribution of endemic species described for the Iberian Peninsula, where mountain ranges exhibit a great diversity of species, at least of the widespread type (Buira et al, 2017). In addition to land-use changes, changes in climate, notably a warming climate, are expected to strongly impact biodiversity in mountain environments Pauli et al, 2012;Stöcklin et al, 2009;Thuiller et al, 2014). Species are expected to migrate upward to keep pace with suitable climates, which should lead to an increase of diversity in higher altitudes in the near term (Walther et al, 2005).…”
Section: Discussionsupporting
confidence: 78%
“…Species are expected to migrate upward to keep pace with suitable climates, which should lead to an increase of diversity in higher altitudes in the near term (Walther et al, 2005). However, it has been demonstrated by Thuiller et al (2014) that those studies carried out at European scales and coarse spatial resolution were not able to correctly account for mountain peculiarities, such as topographic micro-heterogeneity and meso-scale refuges, and that more recent studies have instead shown that when models are applied at high resolution, specifically over mountains, the results are less pessimistic, indicating that mountain floras can persist in some specific areas (Engler et al, 2011;Dullinger et al, 2012;Thuiller et al, 2014). However, changes in climatic conditions in the mountain areas may lead to a translocation of type populations, and this potential risk will require a dedicated study and monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to quantify how climate change would affect mountain biodiversity have either relied on spatial projections of species' climatic niches2021, a combination of niche-based and demographic modelling22 or on spatially explicit dynamic vegetation models23. None of these studies has considered that evolution can co-determine and modify the response of mountain species to climate warming.…”
Section: Introductionmentioning
confidence: 99%
“…Climate projections in mountainous regions, which are motivated by a broad range of geophysical, environmental and societally relevant scientific challenges (Martin et al, 1994;Beniston, 1997;Jomelli et al, 2009;Castebrunet et al, 2014;Piazza et al, 2014;Schmucki et al, 2014;Lafaysse et al, 2014;Boulangeat et al, 2014;Thuiller et al, 2014;Castebrunet et al, 2014;Francois et al, 2015;Spandre et al, 2016) are particularly sensitive to the quality of the adjustment method. Indeed, RCM resolutions typically between 10 and 50 km are not sufficient to capture the fine-scale processes and thresholds at play.…”
Section: Introductionmentioning
confidence: 99%